Moderating role of academic motivation and entitlement between motives of students and academic achievement among university students - Saira Bano; Muhammad Naveed Riaz (Journal of the Pakistan Medical Association, 2023)
Abstract Objectives: To examine the moderating role of academic motivation and entitlements on the academic achievements of university students, and to study the role of sycophancy and excuse-making on the part of students. Method: The descriptive cross-sectional study was conducted at the University of Okara, Okara, Pakistan, from November 2017 to November 2018, and comprised university students from Okara and Sargodha. Data was collected using the Students’ Motives for Communicating with their Instructors Scale, the Academic Motivation Scale and the Academic Entitlement Scale. Data was analysed using SPSS 23. Results: There were 300 students. Academic motivation moderated the relationship between participation motive and academic achievement as well as the relationship between functional motive and academic achievement (p<0.05). Academic entitlement moderated the relationship between relational motive and academic achievement (p<0.05). Conclusion: Students’ negative motives for communicating were influenced by academic entitlement, and positive motives were enhanced with academic motivation. Key Words: Academic achievement, Entitlement, Motivation, Relational, Functional, Participation, Excuse making, Sycophancy.